Multispecies Justice and the Rights of Nature: Resolving Normative Tensions in Ecological Governance - David, Vareba Dinebari (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The escalating planetary crises of biodiversity loss and climate change have catalyzed a profound search for post-anthropocentric paradigms in environmental ethics and law. Two of the most significant movements to emerge are the Rights of Nature (RoN), which seeks to grant legal personhood and standing to ecosystems, and the theoretical framework of Multispecies Justice (MSJ), which calls for a radical re-imagination of justice that includes the flourishing of all biotic and abiotic beings. While often presented as allied projects, this paper argues that a deep and under-examined normative tension exists between them. The Rights of Nature approach, for all its power, is frequently grounded in a Western liberal legal tradition that relies on the concept of discrete, rights-bearing individuals. This can inadvertently codify a static, entity-centric ontology that risks ecological fragmentation and struggles to adjudicate the complex, relational entanglements of living systems. In contrast, Multispecies Justice, drawing from Indigenous cosmologies, post-humanist philosophy, and political ecology, emphasizes relationality, process, and the situated well-being of all constituents within dynamic socio-ecological assemblages. This paper critically analyzes this constitutive tension through a detailed philosophical examination and a comparative analysis of two seminal RoN cases: the Whanganui River (Te Awa Tupua) in Aotearoa New Zealand and the Vilcabamba River in Ecuador. It explores how a rigid rights-based framework can fail to resolve interspecies conflicts and may reinforce the very ontological separations it seeks to overcome. The paper concludes by proposing a synthesized model of “Relational Ecological Governance,” which seeks to integrate the potent legal enforceability of RoN with the nuanced, context-sensitive, and process-oriented ethics of MSJ. This model offers a more robust, ecologically literate, and truly transformative foundation for an Earth jurisprudence capable of navigating the Anthropocene.